Effects of taurine on markers of muscle damage, inflammatory response and physical performance in triathletes - Galan, Bryan S. [UNESP]; Carvalho, Flávia G. [UNESP]; Santos, Priscila C. [UNESP]; Gobbi, Ronaldo B. [UNESP]; Kalva-Filho, Carlos A.; Papoti, Marcelo; Da Silva, Adelino S.; Freitas, Ellen C. [UNESP] (My University, 2018)
BACKGROUND: The practice of prolonged exercise with high intensity, as seen in triathlon training, can cause physiological imbalances that might result in muscle fatigue, muscle damage and changes in systemic inflammatory response, thus reduce the athletes' physical performance, therefore, both adequate total caloric and macronutrient intake also the use of a specific ergogenic aid, as taurine supplementation would be an alternative to prevent inflammation and muscle damage. In order to verify the effects of 8 weeks of taurine and chocolate milk supplementation, markers of muscle damage, inflammation, and aerobic capacity were quantified in triathletes. METHODS: A double-blind, crossover, randomized study was conducted with 9 male long-distance triathletes, aged 25-35 years. Supplementation of 3 g of taurine (TAU) or placebo (PLA) associated with 400 mL low fat chocolate milk was performed during an 8-week period. In order to verify the effects of the supplementation protocol markers of muscle damage as lactate dehydrogenase (LDH) and creatine kinase (CK), and inflammatory markers tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were quantified, also triathletes' performance was evaluated by exhaust test on a treadmill. RESULTS: It was observed a significant increase in taurine and CK plasma levels after TAU supplementation (P=0.02 and P=0.01, respectively). However, LDH concentrations did not differ significantly after the supplementations performed, and there were no changes in physical performance parameters; anaerobic threshold, perceived exertion, heart rate, and the concentrations of IL-6 and TNF-α. CONCLUSIONS: Taurine supplementation did not provide benefits on performance and muscle damage in triathletes.
Keywords: Athletic performance; Chocolate; Dietary supplements; Taurine